Socio-ecosystem Services for Integrated Heritage Assessment (IHA). A new approach to valuing cultural heritage - Manuel Arcila-Garrido; Gema Ramírez-Guerrero; Javier García-Onetti; J. Adolfo Chica-Ruiz (Boletín de la Asociación de Geógrafos Españoles)
This paper introduces a conceptual framework that adapts the ecosystem services approach to identify the benefits of conserving cultural heritage. This novel approach aims to enhance the social valorization of this heritage. The proposed service categorization and classification are based on anthropic units that offer benefits, complementing the existing classification for services provided by biotic and non-biotic units with a systemic perspective. The Common International Classification of Ecosystem Services (CICES) and the European Union project "Mapping and Assessment of Ecosystems and their Services" (MAES) serve as the primary references. The main objective is to transcend the concept of heritage as an object-based, historical, and aesthetic treasure and instead develop a more comprehensive definition that encompasses geographical, physical-natural, social, and cultural dimensions while also recognizing the value of usage. This proposal has been validated through the analysis of over 200 cultural asset cases from the European Union. It paves the way for a new avenue of research to better comprehend and appraise cultural heritage, as well as any man-made structure that provides benefits to society. By utilizing a language equivalent to the benefits associated with natural assets, we aspire to contribute to the advancement of a more integrated and interdisciplinary approach to spatial and urban planning.